A most intriguing lady : a novel - Ferguson, Sarah, Duchess of York, 1959-; Kaye, Marguerite (Avon, an imprint of HarperCollinsPublishers, 2023)
"From Sarah Ferguson, the Duchess of York, a sweeping, romantic compulsively readable historical saga about a Duke's daughter--the perfect Victorian lady--who secretly moonlights as an amateur sleuth for high society's inner circle"--